2015
DOI: 10.1016/j.jsat.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Injection and sexual HIV/HCV risk behaviors associated with nonmedical use of prescription opioids among young adults in New York City

Abstract: Prevalence of nonmedical prescription opioid (PO) use has increased markedly in the U.S. This qualitative study explores the drug-use and sexual experiences of nonmedical PO users as they relate to risk for HIV and HCV transmission. Forty-six New York City young adult nonmedical PO users (ages 18–32) completed in-depth, semi-structured interviews. Despite initial perceptions of POs as less addictive and safer than illegal drugs, PO misuse often led to long-term opioid dependence and transition to heroin use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
115
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 34 publications
9
115
0
1
Order By: Relevance
“…Our findings complement other literature citing social settings as the most common contexts for initiation to non-medical prescription drug use [16], and PO initiation specifically [5,18,21]. Interestingly, our data contained a higher proportion of non-oral initiates that those reported in other prior studies of young adult PO misusers [5,18], suggesting that the use of alternate routes may be more prevalent than previously reported.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings complement other literature citing social settings as the most common contexts for initiation to non-medical prescription drug use [16], and PO initiation specifically [5,18,21]. Interestingly, our data contained a higher proportion of non-oral initiates that those reported in other prior studies of young adult PO misusers [5,18], suggesting that the use of alternate routes may be more prevalent than previously reported.…”
Section: Discussionsupporting
confidence: 87%
“…school, parties) has also been found to influence the decision to initiate; setting, coupled with peer use and exposure, helps to normalize prescription drug abuse, creating comfort in the perception that use is common and fun [16]. Social and environmental contexts have also been found to contribute to transitions to alternative routes of administration, including drug injecting among established illicit PO users [5,10,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, PO residue injection has never been measured or discussed explicitly in epidemiological studies. Yet, in addition to our ethnographic study, PO drug residue injection has been recently qualitatively reported in New York (Mateu-Gelabert et al, 2015), which suggests PO residue injection is not an isolated phenomenon.…”
Section: Introductionsupporting
confidence: 49%
“…Our findings are consistent with other, smaller studies that have found associations between NMUPD and SRBs. [17][18][19][20][21][22] When we investigated interactions between demographic characteristics and the association between NMUPD and SRBs, we observed significant subgroup differences among sex and racial/ ethnic subgroups, but not grade, for several SRBs. The interaction results for race/ethnicity for NMUPD and SRBs is likely due to two factors: black students have a low prevalence of NMUPD compared with white and Hispanic students and also have a higher prevalence of SRBs such as having had sex, having ≥4 lifetime sexual partners, and being currently sexually active.…”
Section: Discussionmentioning
confidence: 91%
“…18 The limited studies on NMUPD and SRBs among adult populations have found an association between NMUPD and SRBs. [20][21][22] This study used nationally representative data to address the research gap in the possible association between NMUPD and SRBs among high school students in the United States. Our primary objectives were to (1) determine if NMUPD is independently associated with SRBs and (2) explore an association by demographic subgroups (eg, sex, race/ethnicity, grade).…”
mentioning
confidence: 99%